Characterization of the emerging recombinant infectious bronchitis virus in China - Wang, Suchun; Pan, Junhui; Zhou, Kaiyutai; Chu, Dianfeng; Li, Jinji; Chen, Yiping; Qi, Qian; Wei, Shimeng; Li, Chao; Sui, Jinyu; Wu, Faxing; Li, Jinping; et al. (Frontiers in Microbiology, 2024)
Infectious bronchitis virus (IBV) can cause serious harm to poultry industry. It is belong to Coronaviridae which is highly variable. A kind of emerging recombinant IBV (ahysx-1) has been detected in chicken from China in 2016. To understand the epidemiology and characterization of the emerging recombinant IBV, 35,455 samples of chickens from the 15 provinces in China were collected and detected. One hundred and ninety-six out of the 537 flocks (positive rate, 36.49%), and 908 out of 35,455 samples (positive rate, 2.56%) were positive in the detection. The results showed that the emerging recombinant IBV was pandemic in China. Thirteen emerging recombinant IBV isolates were selected and continuous subcultured to the fourth generation and analyzed by Next-generation sequencing. Compared with the reported sequence of ahysx-1, the genomic analysis showed that multiple position insertions and deletions were in 1a gene, 3b gene, M gene and N gene. The identity of the S gene nucleotide sequence between all the 13 emerging recombinant IBV isolates and reference stain ahysx-1 were 98.1–99.1%, while the identity of amino acid sequence were 98.0–99.8%. To better understand the recombination mechanism of the emerging recombinant IBV, the genomic sequence of the 13 isolates were compared with turkey coronavirus or guinea fowl coronavirus. The results suggest that all the 13 emerging recombinant IBV isolates were likely to be the recombination of turkey coronavirus or guinea fowl coronavirus with IBV. Turkey coronavirus or guinea fowl coronavirus as minor parents are the donors of S gene. The major parents donors of the genome backone of these recombination events were lineages GI-19 or GVI-1 of IBV. One isolate (IBV/chicken/Henan/H1173/2021) was selected for pathogenicity analysis. The results showed that IBV/chicken/Henan/H1173/2021 was avirulent to SPF embryonated eggs, but could cause intestinal symptoms in of chicks. This study provides a foundation for understanding the epidemic situation and characterization of the emerging recombinant IBV. It is of great significance for the prevention and control of avian coronavirus infection.